Human-ecodynamics and the intertidal zones of the Zanzibar Archipelago - Faulkner, Patrick; Sarathi, Akshay; Crowther, Alison; Smith, Tam; Harris, Matthew; Ali, Abdallah K.; Haji, Othman; LaViolette, Adria; Norman, Neil L.; Horton, Mark; Boivin, Nicole (Frontiers in Earth Science, 2022)
The intertidal zone, covering the nearshore fringe of coasts and islands and extending from the high-water mark to areas that remain fully submerged, encompasses a range of habitats containing resources that are as important to modern populations as they were to humans in prehistory. Effectively bridging land and sea, intertidal environments are extremely dynamic, requiring complexity and variability in how people engaged with them in the past, much as they do in the present. Here we review and reconsider environmental, archaeological, and modern socio-ecological evidence from the Zanzibar Archipelago on eastern Africa’s Swahili coast, focusing on marine molluscs to gain insight into the trajectories of human engagement with nearshore habitats and resources. We highlight the potential drivers of change and/or stability in human-intertidal interactions through time and space, set against a backdrop of the significant socio-economic and socio-ecological changes apparent in the archipelago, and along the Swahili coast, during the late Holocene.